Online accessibility of academic articles and the diversity of economics - Timo Boppart; Kevin E. Staub (University of Zurich, Department of Economics, 2012)
A key aspect of generating new ideas is drawing from different elements of past knowledge and combining them into a new idea. In such a process, the diversity of ideas plays a central role. This paper examines the empirical question of how the internet affected the diversity of new research by making the existing literature accessible online. The internet marks a technological shock which affects how academic scientist search for and browse through published documents. Using article-level data from economics journals for the period 1991 to 2009, we document how online accessibility lead academic economists to draw from a more diverse set of literature for their articles, and to write articles which incorporated more diverse contents.
Keywords: A11; D83; O31; O33; 330; digitization; online publication; bibliometrics; knowledge production function; recombinant growth; citations; networks; scholarly communication; Elektronische Publikation; Wissenschaftliches Arbeiten; Wirtschaftszeitschrift; Bibliometrie; Welt